Knowledge about Maintaining Dental and Oral Hygiene with Dents in the Box Media for Deaf Students in 4-6 Grades at SLB B Karya Mulia Surabaya - Izzakiya Chalida Zain; Silvia Prasetyowati; Sri Hidayati; Bambang Hadi Sugito (International Journal of Advanced Health Science and Technology, 2025)
Maintaining oral and dental hygiene is an important thing for the whole community, especially for vulnerable groups such as deaf children. However, deaf children have difficulty receiving and absorbing information about maintaining oral hygiene due to hearing impairments, which affects their level of understanding. Deaf children have a condition of debris index status in the poor category. This study aims to determine differences in knowledge about maintaining dental and oral hygiene before and after using Dents in the Box media among deaf students in 4-6 grades at SLB B Karya Mulia Surabaya. This research uses a Quasi Experimental type of research: One-Group Pretest-Posttest Group Design with a target number of 28 deaf students. Pre-test and post-test data were collected through questionnaire sheet instruments. The data analysis technique uses the Wilcoxon Test. The results of this study show that there is a difference in knowledge about maintaining dental and oral hygiene before and after using Dents in the Box media among deaf students in 4-6 grades at SLB B Karya Mulia Surabaya. The level of knowledge of deaf students is in the good category after using Dents in the Box media.